Implementasi Algoritma Fuzzy Tsukamoto Dalam Menentukan Harga Jual Udang Pada Tambak Udang Desa Linau Kabupaten Kaur - Topan Samudra; Ujang Juhardi; Muhammad Husni Rifqo; Yulia Darmi Yulia Darmi (UNIVED Press, 2024)
Shrimp is one of the high-value fishery commodities. Apart from being used to meet domestic needs, shrimp are also produced for export purposes. As a leading commodity in the fisheries sector, market dynamics are often unstable, so fluctuations in prices cannot be avoided, including the shrimp ponds in Linau Village, Kaur Regency.The current problem is that the process of determining the selling price in the shrimp ponds of Linau Village, Kaur Regency is still done manually which has the potential to trigger errors in determining the selling price which can be detrimental to the company. Fuzzy logic is a control system methodology for solving problems in systems, ranging from simple systems to complex or complex systems. In the Tsukamoto method, each rule is represented by a fuzzy set with a monotonous membership function called fuzzification. As a result, the output of each rule is in the form of a crisp value based on the α-predicate or the minimum value of each rule and the z value. The final result is obtained by performing a weighted average defuzzification. research has succeeded in making a shrimp pricing system by applying the Fuzzy Tsukamoto method in the analysis and calculation process.